Interface engineering of heterostructured electrocatalysts towards efficient alkaline hydrogen electrocatalysis - Zhao, Guoqiang; Jiang, Yinzhu; Dou, Shi-Xue; Sun, Wenping; Pan, Hongge (Science bulletin, 2021)
This review summarized the recent advances of interface engineering of heterostructured electrocatalysts toward efficient hydrogen electrocatalysis in alkaline media. Interface engineering could not only induce synergistic effect but also improve the intrinsic activity and increase the number of active sites. This review would provide insightful ideas toward rational design of electrocatalysts for alkaline hydrogen electrocatalysis. [Display omitted] Boosting the alkaline hydrogen evolution and oxidation reaction (HER/HOR) kinetics is vital to practicing the renewable hydrogen cycle in alkaline media. Recently, intensive research has demonstrated that interface engineering is of critical significance for improving the performance of heterostructured electrocatalysts particularly toward the electrochemical reactions involving multiple reaction intermediates like alkaline hydrogen electrocatalysis, and the research advances also bring substantial non-trivial fundamental insights accordingly. Herein, we review the current status of interface engineering with respect to developing efficient heterostructured electrocatalysts for alkaline HER and HOR. Two major subjects—how interface engineering promotes the reaction kinetics and what fundamental insights interface engineering has brought into alkaline HER and HOR—are discussed. Specifically, heterostructured electrocatalysts with abundant interfaces have shown substantially accelerated alkaline hydrogen electrocatalysis kinetics owing to the synergistic effect from different components, which could balance the adsorption/desorption behaviors of the intermediates at the interfaces. Meanwhile, interface engineering can effectively tune the electronic structures of the active sites via electronic interaction, interfacial bonding, and lattice strain, which would appropriately optimize the binding energy of targeted intermediates like hydrogen. Furthermore, the confinement effect is critical for delivering high durability by sustaining high density of active sites. At last, our own perspectives on the challenges and opportunities toward developing efficient heterostructured electrocatalysts for alkaline hydrogen electrocatalysis are provided.